HUBUNGAN DUKUNGAN IBU DENGAN KECEMASAN REMAJA DALAM MENGHADAPI MENARCHE DI SD NEGERI LOMANIS 01 KECAMATAN CILACAP TENGAH KABUPATEN CILACAP - Nilawati, Ida; ., Sumarni; Santjaka, Aris (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
Abstract: Menarche is the event when a young woman experiencing menstruation or monthly bleeding the first time, this causes anxiety in some young women. Mother is the closest figure for young women between the families so that communication on sensitive matters will be more open to relativism, the position of a mother's role is to support young women face menarche is needed in order to reduce anxiety.Knowing the relationship between maternal support in dealing with teen angst at menarcheLomanis Elementary School District 01 Middle Cilacap Cilacap regency in 2013. This study is a survey research with cross sectional analytic. The samples in this study were young women class IV, V and VI in Lomanis Elementary School District 01 Middle Cilacap Cilacap as many as 37 people. Methods of data analysis using the Spearman rank test and frequency distribution. The majority of support for teenage mothers in the face of menarche in the support category (62,2%). The majority of teenage angst in the face of menarche in the medium category (56,8%). There is a relationship between maternal support in dealing with teen angst at menarche Lomanis Elementary School District 01 Middle Cilacap, Cilacap regency in 2013 in the medium category (p = 0,005 ; ï² = -0,456). There is a relationship between maternal support with teenage angst in the face of menarche. Young women should look for information, could the older adults, the mass media, the internet and asking teachers in the school regarding reproductive health, especially related to menarche. Therefore, when faced later menarcheyoung women are not prone to anxiety and fear to the changes or the arrival of the experienced menarche.Keywords :Adolescents, menarche, maternal support, anxiety